Genetic diversity and molecular identification of mosquito species in the Anopheles maculatus group using the ITS2 region of rDNA - C. Walton (2018)
The species diversity and genetic structure of mosquitoes belonging to the Anopheles maculatus group in Southeast Asia were investigated using the internal transcribed spacer 2 (ITS2) of ribosomal DNA (rDNA). A molecular phylogeny indicates the presence of at least one hitherto unrecognised species. Mosquitoes of chromosomal form K from eastern Thailand have a unique ITS2 sequence that is 3.7% divergent from the next most closely related taxon (An. sawadwongporni) in the group. In the context of negligible intraspecific variation at ITS2, this suggests that chromosomal form K is most probably a distinct species. Although An. maculatus sensu stricto from northern Thailand and southern Thailand/peninsular Malaysia differ from each other in chromosomal banding pattern and vectorial capacity, no intraspecific variation was observed in the ITS2 sequences of this species over this entire geographic area despite an extensive survey. A PCR-based identification method was developed to distinguish five species of the group (An. maculatus, An. dravidicus, An. pseudowillmori, An. sawadwongporni and chromosomal form K) to assist field-based studies in northwestern Thailand. Sequences from 187 mosquitoes (mostly An. maculatus and An. sawadwongporni) revealed no intraspecific variation in specimens from Thailand, Cambodia, mainland China, Malaysia, Taiwan and Vietnam, suggesting that this identification method will be widely applicable in Southeast Asia. The lack of detectable genetic structure also suggests that populations of these species are either connected by gene flow and/or share a recent common history. © 2006 Elsevier B.V. All rights reserved.